2012
DOI: 10.1200/jco.2012.30.15_suppl.e21064
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 expression in lung cancer.

Abstract: e21064 Background: Interleukin-15 (IL-15) is a pro-inflammatory cytokine that stimulates the differentiation and proliferation of T, B, and NK cells. IL-15 is normally tightly bound by its receptor, IL-15Rα. Dendritic cells and monocytes/macrophages primarily express both IL-15 and IL-15-Rα; however, expression has been detected on epithelial cells including those of the lung. In the lung, IL-15 is thought to play a role in the induction of immune responses to infection. Over expression of IL-15 has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…29 30 We analyzed the link between IL-15 and effector function-associated molecules using RNA-seq data from The Cancer Genome Atlas (TCGA) database, which includes 571 cases adenocarcinoma, 444 cases squamous carcinoma and 109 cases normal lung tissues. We found that the expression level of IL-15 in tumors was significantly lower than that of normal lung tissues (p<0.0001; online supplementary figure S7A), which was consistent with a previous report by Adhami et al 31 Moreover, the expression levels of IL-15 in tumor specimens were strongly correlated with T-cell effector functionassociated molecules such as IFNG, GZMB and PRF1 (online supplementary figure S7B-D). The representative of Ki-67 expression in CD8 + CD57and CD8 + CD57 + T cells from lymph nodes ex vivo (A) (n=5) and after in vitro stimulation with aCD3 and aCD28 mAbs (B) (n=3).…”
Section: Discussionsupporting
confidence: 91%
“…29 30 We analyzed the link between IL-15 and effector function-associated molecules using RNA-seq data from The Cancer Genome Atlas (TCGA) database, which includes 571 cases adenocarcinoma, 444 cases squamous carcinoma and 109 cases normal lung tissues. We found that the expression level of IL-15 in tumors was significantly lower than that of normal lung tissues (p<0.0001; online supplementary figure S7A), which was consistent with a previous report by Adhami et al 31 Moreover, the expression levels of IL-15 in tumor specimens were strongly correlated with T-cell effector functionassociated molecules such as IFNG, GZMB and PRF1 (online supplementary figure S7B-D). The representative of Ki-67 expression in CD8 + CD57and CD8 + CD57 + T cells from lymph nodes ex vivo (A) (n=5) and after in vitro stimulation with aCD3 and aCD28 mAbs (B) (n=3).…”
Section: Discussionsupporting
confidence: 91%
“…For example, IL-10 is able to favor tumor growth both directly by affecting the tumor cells and indirectly by inhibiting immune cells 41 . Interleukin-15 (IL-15), a key pro-inflammatory cytokine 42 , can induce NK cell activation and cytotoxic T-lymphocyte responses leading to tumor regression 43 .…”
Section: Discussionmentioning
confidence: 99%
“…41 Interleukin-15 (IL-15), a key proinflammatory cytokine, 42 can induce NK cell activation and cytotoxic T-lymphocyte responses leading to tumor regression. 43 PET tumor radiomics can help predict response in NSCLC. 44 Yang et al found that GLSZM-LZLGE exhibited significant temporal changes in partial metabolic responders.…”
Section: D Identification Of Important Features and "Crosstalk" Frmentioning
confidence: 99%